2020
DOI: 10.1111/ppc.12533
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality among young adults: The role of anxiety, depression, musculoskeletal pain, and low dietary calcium intake

Abstract: This study examined the relationships between sleep quality, anxiety, depression, musculoskeletal pain (MSP), and calcium intake. Design and Methods: In this cross-sectional study (N = 1422), sleep was assessed using the Pittsburgh Sleep Quality Index, anxiety and depression were assessed using the Hospital Anxiety and Depression Scale, and calcium intake and MSP were assessed by self-reporting. Findings: Poor sleep quality was reported by 62.66% of the participants. The participants with poor sleep quality re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…In our previous cross sectional study that involve 1422 students' ages between 18-29 years, poor sleep quality was reported by 62.66% of the participants (Alkhatatbeh et al, 2021). In addition, the participants with poor sleep quality reported lower daily calcium intake, higher anxiety and depression levels, more severe MSP.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In our previous cross sectional study that involve 1422 students' ages between 18-29 years, poor sleep quality was reported by 62.66% of the participants (Alkhatatbeh et al, 2021). In addition, the participants with poor sleep quality reported lower daily calcium intake, higher anxiety and depression levels, more severe MSP.…”
Section: Discussionmentioning
confidence: 85%
“…Daily calcium intake was determined as previously described (Alkhatatbeh, Abdul-Razzak, & Khwaileh, 2021). In brief, participants were asked questions regarding their daily frequency and type of dairy products intake (milk, yogurt, cheddar cheese, cream cheese, and labaneh, which is a soft cream cheese made by removing whey from yogurt with a cheese cloth).…”
Section: Assessment Of Daily Calcium Intakementioning
confidence: 99%
See 3 more Smart Citations